2014
DOI: 10.1007/s12020-014-0435-3
|View full text |Cite
|
Sign up to set email alerts
|

Leptin at gender-specific concentrations does not affect glucose transport, expression of glucose transporters and leptin receptors in human lymphocytes

Abstract: Leptin shows pleiotropic effects in organisms including an important role in the regulation of glucose homeostasis. Elevated serum leptin, particularly in obese individuals, is a warning sign of energy imbalance, hyperinsulinemia, insulin resistance and other metabolic risk factors that are strongly associated with type 2 diabetes. Obesity is also related to a higher rate of infections and immune function deterioration may in part ensue from decreased glucose uptake as the main energy source for lymphocytes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Following lymphocyte activation, ObR expression shifted to a higher intensity and density ( 26 ). ObR expression, particularly that of the long isoform, in normal murine thymocytes is exceedingly low or negative ( 27 ). However, the present study revealed that Jurkat and MOLT-3 cells, which are suspected to develop from thymocytes or thymic progenitors, exhibit a high expression level of ObR.…”
Section: Discussionmentioning
confidence: 99%
“…Following lymphocyte activation, ObR expression shifted to a higher intensity and density ( 26 ). ObR expression, particularly that of the long isoform, in normal murine thymocytes is exceedingly low or negative ( 27 ). However, the present study revealed that Jurkat and MOLT-3 cells, which are suspected to develop from thymocytes or thymic progenitors, exhibit a high expression level of ObR.…”
Section: Discussionmentioning
confidence: 99%
“…In our experiments, TGF- β 1 protein levels were significantly higher in db/db mice than in mice in the other groups. This finding suggests that the cell hypertrophy observed in the db group was related to the high expression level of TGF- β 1, which can block ECM degradation [ 26 , 27 ]. Matrix metalloproteinases (MMPs) are enzymes that play key roles in substrate degradation.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely involved in the regulation of various physiological activities of the human body, such as food intake, energy consumption and metabolism, hormone regulation, immunity, and vascular proliferation [ 62 ]. The levels of leptin, as a negative feedback signal of central fat deposition in the brain, increase with increasing fat deposition [ 63 , 64 ]. A study found that human plasma leptin levels and phenylalanine concentrations are positively correlated [ 65 ].…”
Section: Discussionmentioning
confidence: 99%